Dipeptidyl peptidase-4 inhibition with linagliptin and effects on hyperglycaemia and albuminuria in patients with type 2 diabetes and renal dysfunction: Rationale and design of the MARLINA–T2D™ trial. (November 2015) - Groop, Per-Henrik; Cooper, Mark E; Perkovic, Vlado; Sharma, Kumar; Schernthaner, Guntram; Haneda, Masakazu; Hocher, Berthold; Gordat, Maud; Cescutti, Jessica; Woerle, Hans-Juergen; von Eynatten, Maximilian
Efficacy, Safety & M odification of A lbuminuria in Type 2 Diabetes Subjects with R enal Disease with LINA gliptin (MARLINA–T2D™), a multicentre, multinational, randomized, double-blind, placebo-controlled, parallel-group, phase 3b clinical trial, aims to further define the potential renal effects of dipeptidyl peptidase-4 inhibition beyond glycaemic control. A total of 350 eligible individuals with inadequately controlled type 2 diabetes and evidence of renal disease are planned to be randomized in a 1:1 ratio to receive either linagliptin 5 mg or placebo in addition to their stable glucose-lowering background therapy for 24 weeks. Two predefined main endpoints will be tested in a hierarchical manner: (1) change from baseline in glycated haemoglobin and (2) time-weighted average of percentage change from baseline in urinary albumin-to-creatinine ratio. Both endpoints are sufficiently powered to test for superiority versus placebo after 24 weeks with α = 0.05. MARLINA–T2D™ is the first of its class to prospectively explore both the glucose- and albuminuria-lowering potential of a dipeptidyl peptidase-4 inhibitor in patients with type 2 diabetes and evidence of renal disease.